Constraints on relativistic jets in quiescent black hole X-ray binaries from broad-band spectral modelling - Plotkin, R.; Gallo, E.; Markoff, S.; Homan, J.; Jonker, P.; Miller-Jones, James; Russell, D.; Drappeau, S. (OXFORD UNIV PRESS, 2015)
The nature of black hole jets at the lowest detectable luminosities remains an open question, largely due to a dearth of observational constraints. Here, we present a new, nearly simultaneous broad-band spectrum of the black hole X-ray binary (BHXB) XTE J1118+480 at an extremely low Eddington ratio (LX ~ 10−8.5LEdd). Our new spectral energy distribution (SED) includes the radio, near-infrared, optical, ultraviolet, and X-ray wavebands. XTE J1118+480 is now the second BHXB at such a low Eddington ratio with a well-sampled SED, thereby providing new constraints on highly sub-Eddington accretion flows and jets, and opening the door to begin comparison studies between systems. We apply a multizone jet model to the new broad-band SED, and we compare our results to previous fits to the same source using the same model at 4–5 decades higher luminosity.We find that after a BHXB transitions to the so-called quiescent spectral state, the jet base becomes more compact (by up to an order of magnitude) and slightly cooler (by at least a factor of 2). Our preferred model fit indicates that jet particle acceleration is much weaker after the transition into quiescence. That is, accelerated non-thermal particles no longer reach high enough Lorentz factors to contribute significant amounts of synchrotron X-ray emission. Instead, the X-ray waveband is dominated by synchrotron self-Compton emission from a population of mildly relativistic electrons with a quasi-thermal velocity distribution that are associated with the jet base. The corresponding (thermal) synchrotron component from the jet base emits primarily in the infrared through ultraviolet wavebands. Our results on XTE J1118+480 are consistent with broad-band modelling for A0620-00 (the only other comparably low Eddington ratio BHXB with a well-sampled SED) and for Sgr A* (the quiescent supermassive black hole at the Galactic centre). The above could therefore represent a canonical baseline geometry for accreting black holes in quiescence. We conclude with suggestions for future studies to further investigate the above scenario.